Pengaruh Faktor Internal dan Eksternal terhadap Pertumbuhan Laba pada Bank Umum Swasta Nasional (BUSN) Non Devisa Periode 2014-2018 - Utami, Andini Estikarti (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Banks in Indonesia are required to do their own assessment by using a risk-based bank rating based on RGEC – Risk Profile, GCG, Earnings, and Capital. The goal of this research is to analyze the leverage of internal and external factors on the profit growth of non-foreign exchange national private commercial banks in 2014-2018. This research is a causal study with purposive sampling technique, so that 21 banks sample are obtained. The analysis method used in this research is multiple linear regression analysis. In this study, it was found that there was a simultaneous influence between the independent variables on profit growth. Partially, only LDR has a positive and significant effect on profit growth. When LDR ratio increases, profit growth will also increase which means that operational activities have been running efficiently and the bank can fulfill its obligations to creditors. Meanwhile, the other variables such as NPL, GCG, ROA, BOPO, CAR, and inflation do not affect on profit growth.